Gene and protein microarrays: tools for gene discovery and function - Tomlinson, Craig R. (Henry Stewart Talks, 2007)
High-throughput methods to examine global gene expression, Understanding interactions in a given cell, tissue and organism under normal and disease state conditions, Application of high throughput methods used in genomics and proteomics, Use of DNA and protein microarrays for gene discovery and function, Background information and terminology used in genomics and proteomics, How DNA and protein microarrays are carried out, Predicted future direction of genomics and proteomics microarray technologies
Archived at 2020/08/13